Deciphering a missing piece of the branched-chain amino acids uptake puzzle: YhjE is an L-isoleucine and L-valine transporter in Escherichia coli K-12 - Molev, Sergey V.; Stepanova, Agnessa A.; Vybornaya, Tatiana V.; Khozov, Andrey A.; Surkov, Makar M.; Badun, Gennadii A.; Chernysheva, Maria G.; Netrusov, Alexander I.; Yanenko, Alexander S.; Sineoky, Sergey P.; Bubnov, Dmitrii M. (Frontiers in Microbiology, 2025)
Branched-chain amino acid (BCAA) uptake in bacteria underpins fitness, pathogenesis, and industrial strain performance, yet the transport landscape, even in Escherichia coli, remains incomplete. Here, we identify and characterize YhjE as a BCAA permease specific for L-isoleucine and L-valine. Selection for L-valine–resistant clones in a ΔlivKHMGF ΔbrnQ background repeatedly recovered mutations in yhjE, indicating that YhjE mediates L-valine entry. Deletion of yhjE in the ΔlivKHMGF ΔbrnQ background increased the L-isoleucine requirement and raised the minimal inhibitory concentration of L-valine, whereas the L-leucine requirement was unaffected. Direct uptake assays showed that YhjE mediates L-isoleucine and L-valine import. Kinetic analysis yielded apparent KM values of 70.5 μM (L-isoleucine) and 86.7 μM (L-valine), establishing YhjE as a lower-affinity system compared with LIV-I (encoded by the livKHMGF operon and livJ gene) and BrnQ. Energetically, transport was proton-motive-force–dependent: the protonophore carbonyl cyanide m-chlorophenyl hydrazone strongly inhibited uptake, and L-isoleucine addition elicited proton influx as observed by pH measurements. Analysis of transcriptional regulation revealed strict dependence of yhjE promoter activity on Lrp and repression by L-leucine, L-methionine, and L-isoleucine, indicating nutrient-responsive control. Hydroxylamine mutagenesis yielded yhjE variants that permitted growth under L-leucine limitation; across tested alleles, L-leucine uptake increased while L-isoleucine uptake decreased, demonstrating reprogramming of substrate preference via discrete substitutions. Finally, a ΔlivKHMGF ΔbrnQ ΔyhjE triple mutant showed no detectable uptake of L-isoleucine and L-valine at substrate concentrations up to 100 μM, implying that if other routes exist, their contribution at physiological substrate levels is negligible.